Conditional survival in patients with spontaneous tumor rupture of hepatocellular carcinoma after partial hepatectomy: a propensity score matching analysis. Issue 6 (June 2019) - Zhu, Qian; Qiao, Guoliang; Xu, Chang; Yu, Xiaojin; Zhao, Jing; Yu, Zeqian; Hu, Minjie; Yang, Yang; Wang, Lishan; Lu, Miao; Hu, Fangfang; Cheng, Zhangjun; et al.
Abstract: Background: Spontaneous tumor rupture (STR) of hepatocellular carcinoma (HCC) is a life-threatening condition. This study investigates the influences of STR on the observed survival and conditional survival of patients received hepatectomy. Methods: A retrospective cohort of patients who underwent hepatectomy from 2009 to 2013 was divided into tumor rupture group and non-rupture group. Propensity score matching (PSM) was used for comparison of the observed survival and conditional survival probabilities between these two groups. Results: 89 pairs of patients who had comparable background and tumor characteristics were created using PSM analysis. There was significant association between STR and increased risk of OS no matter when before or after PSM (p < 0.01). STR was significantly associated with increased risks of PFS before, while not after PSM. Multivariate Cox regression analyses demonstrated that STR was an independent risk factor associated with OS. There were significant differences in two groups for conditional probabilities of OS and PFS for an additional 6 months and 1 year before PSM, while not after PSM. Conclusions: This study identified STR but not PFS as an independent risk factor influencing OS, in patients with HCC following hepatectomy. In selected patients with STRHCC, hepatectomy should be performed with acceptable outcomes.